OC-131 Pattern of recurrence following non-anatomical resection for colorectal liver metastasis. (28th May 2012) - Hakeem, A; Marangoni, G; Nair, A; Young, R; Hidalgo, E; Toogood, G; Lodge, J P A; Prasad, K R
Abstract : Introduction: Non-anatomical resection (NAR) for colorectal liver metastasis (CRLM) has become more common in an attempt to preserve liver parenchyma. Pattern of recurrence (POR) following NAR has been reported previously, but there has been no detail on the hepatic recurrences with respect to previous NAR. We aim to investigate pattern of hepatic recurrence in patients who underwent NAR for CRLM, especially looking at the recurrences in the context of previous resected segment. Methods: 1580 CRLM resection were performed in our centre between 1993 and 2010. 591 (37.4%) were NAR and 989 (62.6%) were AR. Patients who underwent simultaneous Anatomical Resection (AR) were excluded (95 out of 591). All NAR were grouped as either unilobar or bilobar metastatectomy and POR studied in relation to previous resected segment. Results: 495 NAR were included. There were 291 recurrences (58.7%). 188 were hepatic (37.9%) and 103 extra-hepatic (20.8%). In 11 patients with hepatic recurrence, data were not available for recurrence segment and therefore excluded from POR analysis. The POR following unilobar metastatectomy (n=127): same segment (n=32, 25.2%), same sector (n=9, 7.1%), ipsilateral hemi-liver (n=48, 37.8%), contralateral hemi-liver (n=15, 11.8%) and bilobar (n=23, 18.1%). The POR following bilobar metastatectomy (n=50): same segment (n=1, 2%), hemi-liver with equal number of segments resected previously (n=15, 30%), hemi-liver with lesser involved segments previously (n=7, 14%), hemi-liver with more segment involved previously (n=10, 20.0%) and bilobar (n=17, 34.0%). Conclusion: This retrospective study shows that following unilobar CRLM resections, 70.0% recur in the ipsilateral hemi-liver. In bilobar resections, 22.0% recur in the same segment or hemi-liver with previous multiple resections. Our data supports a more aggressive approach for unilobar disease. Further studies need to be done on pattern of recurrences in patients undergoing parenchyma preserving surgery to develop best surgical strategies. Competing interests: None declared.